Democratic Leadership Of The Foundation Chairman And Work Motivation On Teacher Performance At The Sabilush Sholihin Foundation Of Islamic Education And Dakwa Bangkalan District - Mahyadi Mahyadi; Iriani Ismail (Brilliant International Journal Of Management And Tourism, 2023)
Several factors that influence teacher performance include democratic leadership and work motivation. This study took the object of the Sabilush Sholihin Islamic Education and accusations Foundation, Socah Village, Bangkalan Regency. This study uses a qualitative method with a population of 63 teachers. The aims of this study were 1) to determine the effect of democratic leadership style on teacher performance at the Islamic education foundation and accusations sabilush sholihin, Socah district, Bangkalan district. 2) To determine the effect of work motivation on the performance of teachers at the Islamic education foundation and accusations Sabilush Sholihin, Socah district, Bangkalan district. 3) to determine the simultaneous effect of democratic leadership and work motivation on teacher performance at the Sabilush sholihin Islamic education and accusations foundation, Socah district, Bangkalan district. 4) To find out which variables of democratic leadership style and work motivation have the dominant influence on teacher performance in educational and educational foundations. Accusations Sabilush Sholihin, Socah district, Bangkalan district. Based on the results of statistical tests, it was found that 1) democratic leadership style had a positive and significant effect on the teacher’s performance variable at the Sabilush Sholihin Islamic accusations Foundation and Education. It is shown that the result of the t-test calculation is tcount (6.646) > ttable (1.99962) with a significant value of 0.000 <0.05. 2) work motivation has a positive and significant effect on the teacher’s performance variable at the Sabilush Sholihin Islamic Da’wah Foundation and Education. It is shown that the result of the t-test calculation is tcount (3.203) > ttable (1.99962) with a significant value of 0.002 <0.05. 3) Together or simultaneously the independent variables (democratic leadership style and work motivation) have a positive and significant effect on the dependent variable (Teacher Performance at the Sabilush Sholihin Islamic accusations Foundation and Education). It is shown that the result of the F test calculation is Fcount (143.450) > Ftable (3.15) with a significant value of 0.000 <0.05. 4) democratic leadership style that has a dominant influence on the teacher's performance variable at the Sabilush Sholihin Islamic accusations Foundation and Education